Dr. Noormazlinah smart SSB research produces additional nutrients for plants - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PAYA BESAR, 1 December 2022 - Lecturer from the Faculty of Chemical and Process Engineering Technology (FTKKP), Dr. Noormazlinah Ahmad managed to formulate a product that combines oleochemical solid waste and prebiotics that can provide good and nutritional supplementation to crops.